(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
In the article, biological integrity develops on the basis of general social laws and is divided into many groups at the same time. We conclude that each tribe, nation, nation in a certain historical period has a number of psychological characteristics that are characteristic of this ethnic group, which are not characteristic of another group or to a lesser extent